Question Words Teaching Strategy in Grade 5 of SD Negeri 104267 Pegajahan - Lubis, Fawwazatul Ulfa; Simanjuntak, Eva Betty; Zahra, Khaira Laini; Panggabean, Revalina; Nasution, Chindy Abelia; Turnip, Halimatu Zahra (CV. PUSDIKRA MITRA JAYA, 2025)
English language education at SD Negeri 104267 Pegajahan emphasizes the importance of mastering question words such as “what,” “who,” “where,” “when,” “why,” and “how,” which form the basis for students' communication skills. This study aims to analyze the teaching strategies used by teachers and the challenges faced during the learning process. The method applied is qualitative descriptive, with data collection through in-depth interviews and literature review. The results of the study indicate that contextual and interactive teaching methods are effective in improving students' understanding of the use of question words. However, challenges remain, such as limited learning time and differences in students' abilities. It is hoped that teachers can integrate technology and implement project-based learning to increase students' motivation and engagement. With continued support, it is hoped that students will be able to communicate with greater confidence and effectiveness and be motivated to continue learning English in the future.